Pengaruh External Pressure, Financial Targets dan Financial Stability terhadap Financial Statement Fraud - Sari, Andini Mustika; Anjilni, Ratih Qadarti (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
This study investigates the influence of external pressure, financial targets, and financial stability on financial statement fraud in transportation and logistics companies listed on the Indonesia Stock Exchange during 2020-2023. Financial statement fraud has become a critical issue due to its potential to mislead stakeholders and damage corporate credibility. Using purposive sampling, 10 companies were selected, resulting in 40 firm-year observations. Secondary data were obtained from audited financial reports and analyzed using multiple linear regression with Eviews 12. The findings reveal that external pressure and financial targets do not have a significant effect on financial statement fraud when tested individually. In contrast, financial stability shows a significant negative relationship with financial statement fraud, indicating that unstable financial conditions increase the likelihood of manipulation in financial reporting. Simultaneously, the three variables significantly influence financial statement fraud with an explanatory power of 43.75%. These results highlight the importance of monitoring financial stability as an early indicator of fraudulent practices, while also suggesting that external pressure and financial targets may not always drive fraudulent reporting in this sector.